2011
DOI: 10.1080/15257770.2011.607145
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Oligonucleotide-Conjugated Pyrrole Polyamide-2′-Deoxyguanosine Hybrids as Novel Gene Expression Control Compounds

Abstract: DNA oligonucleotide-conjugated pyrrole polyamide-2'-deoxyguanosine hybrids were synthesized and examined as novel gene expression control compounds. The T(m) values and circular dichroism spectral analyses showed that the oligonucleotide-conjugated hybrids possess high DNA recognition and a very high binding affinity for DNA that includes the pyrrole polyamide binding sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…DNA oligonucleotides were purchased from Hokkaido System Science Co., Ltd. Compounds 2 , 3 , 4 , 5 , 7 , 9, and 12 were prepared as previously described [ 9 13 ]. The CPG support-bound 2′-deoxynucleoside 16 (B = C Bz ) and 2′-deoxynucleoside 3′-phosphoramidites 17 (B = T, C Bz , A Bz , and G iBu ) were purchased from Glen Research Corporation.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…DNA oligonucleotides were purchased from Hokkaido System Science Co., Ltd. Compounds 2 , 3 , 4 , 5 , 7 , 9, and 12 were prepared as previously described [ 9 13 ]. The CPG support-bound 2′-deoxynucleoside 16 (B = C Bz ) and 2′-deoxynucleoside 3′-phosphoramidites 17 (B = T, C Bz , A Bz , and G iBu ) were purchased from Glen Research Corporation.…”
Section: Methodsmentioning
confidence: 99%
“…It was shown that Hybrid 1 possessed greater binding specificity compared with distamycin A [ 12 ]. Then, in an effort to examine the development of potential antisense drugs, we synthesized oligonucleotide ON 1 ( n = 3) conjugated to Hybrid 2 in lieu of Hybrid 1 containing the formyl group which is unstable under the basic conditions of deprotection during oligonucleotide solid-phase synthesis, and subsequently examined the binding ability of ON 1 ( n = 3) to complementary DNA ( Figure 2 ) [ 13 ]. Dervan et al [ 14 ], Zamecnik et al [ 15 ], Novopashina et al and Boutorine et al [ 16 21 ] have reported the synthesis and evaluation of oligonucleotides conjugated with one or two MGB polyamides to either the 5′- or 3′-ends.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some nucleoside analogs have been used in preclinical studies for several therapeutic indications including anticancer activity (Shi and Schinazi, 2001;Kawashima et al, 2011;Chen et al, 2012;Van Poecke et al, 2012).…”
Section: Introductionmentioning
confidence: 99%